MENENTUKAN FORMULASI ASURANSI JIWA DWIGUNA MENGGUNAKAN HUKUM HELIGMAN-POLLARD DENGAN KASUS MULTIPLE LIFE - Wanari Intan Dwi Putri; Muhammad Subhan; Dewi Murni (Journal of Mathematics UNP, 2018)
Abstract – One of the problems that can happen to the insurance company is the inability of the company to pay compensation to the insurance participants in the event of a claim. For that, it takes a formulation of premium calculation so that the premium value can be calculated properly. Calculation of net premium using Heligman-Pollard law. The calculation of premiums by using Heligman-Pollard law begins with creating mortalitaas tables, making the cash value of dual-purpose annuity insurance with dependents for n years, calculating net periodic premiums on dual life insurance with multiple life cases, calculating annual net premiums on dual-life insurance with multiple cases life. By using this Heligman-Pollard law, insurance premiums will be grouped into 3 age groups on the new mortality table.